The Effectiveness of Cognitive Behavioral Therapy Group Counseling with Self-Talk and Socratic Dialogue Techniques to Improve Students' Career Self-Efficacy - Septian Nurul Istiqomah; Mulawarman Mulawarman; Anwar Sutoyo (Jurnal Bimbingan Konseling, 2024)
Low career self-efficacy often misleads students career planning. That way motivated this research to examine the effectiveness of cognitive behavioral therapy group counselling with self-talk and socratic dialogue techniques to improve students’ career self-efficacy. The method research make quasi-experimental and involved a two-group pretest-posttest design with which all were experimental groups. The research have 16 students with low career self-efficacy were grouped into two equally. Based on the findings, the intervention of cognitive behavioral therapy group counselling with self-talk and socratic dialogue techniques has been able to effectively improve students’ career self-efficacy. The implication a research guidance and counselling services can refer to this.